2022
DOI: 10.1007/s12144-022-04086-8
|View full text |Cite
|
Sign up to set email alerts
|

How trait gratitude relates to teachers’ burnout and work engagement: job demands and resources as mediators

Abstract: The benefits of gratitude in the workplace, in general, and for teachers, in particular, are still understudied. In the present study, we investigated whether teachers’ trait gratitude is linked to their work engagement and burnout. Moreover, we explored whether perceived job demands and job resources mediate the relation between employees’ gratitude and these two outcomes. A sample of 312 Romanian teachers participated in the study. Participants filled out questionnaires assessing trait gratitude, perceived j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 76 publications
0
1
0
Order By: Relevance
“…In this case, gratitude has a significant role in fighting against the formation of academic burnout as a big problem for Indonesian education program. It can be said that individuals with high gratitude are less to have negative emotions including academic burnout and depersonalization (Nicuță et al, 2022). Therefore it can be said that gratitude can be used as a factor that needs to be improved to prevent academic burnout from occurring in student (Yukhymenko-Lescroart, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In this case, gratitude has a significant role in fighting against the formation of academic burnout as a big problem for Indonesian education program. It can be said that individuals with high gratitude are less to have negative emotions including academic burnout and depersonalization (Nicuță et al, 2022). Therefore it can be said that gratitude can be used as a factor that needs to be improved to prevent academic burnout from occurring in student (Yukhymenko-Lescroart, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Gratitud en el trabajo Recursos sociales del puesto Recursos estructurales del puesto Adaptación del puesto al empleado Teoría "ampliar y construir" Modelo de exigencias-recursos del puesto Gratitude was previously shown to be linked to important positive outcomes for the employees and their organizations. Such benefits include increased job satisfaction, self-reported performance (e.g., Cain et al, 2019;Komase et al, 2020), as well as decreased burnout (e.g., Kersten et al, 2022;Nicu et al, 2022). However, the exploration of this topic has just started in the literature (Locklear et al, 2022).…”
Section: Palabras Clavementioning
confidence: 99%
“…In their longitudinal study, gratitude predicted perceived social support in a sample of Chinese adolescents who were exposed to the Wenchuan earthquake. A number of studies conducted in the work context also argued that trait gratitude helps employees build more social resources in their jobs (e.g., Chen et al, 2021;Feng & Yin, 2021;Nicu et al, 2022). Although these studies found that gratitude positively predicted social support, they did not measure workspecific gratitude and were not longitudinal.…”
Section: The Effect Of Employees' Gratitude On Job Resourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have identified a longitudinal association between gratitude and engagement in education and work settings (Qing et al, 2021; Zhen et al, 2021). Grateful individuals tend to be highly engaged in their work (Komase, Watanabe, Sasaki, & Kawakami, 2021), and gratitude is positively associated with school teachers’ job resources, which in turn increase their work engagement (Nicuţă et al, 2022). These findings indicate that gratitude may be associated with subjective well-being and volunteer retention through volunteer engagement.…”
Section: Introductionmentioning
confidence: 99%